Profile of Maternal Referral Cases - Junita Indarti; Dwiyana Ocviyanti; Reyhan Aditya (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To explore the demography of maternal referral cases in Dr. Cipto Mangunkusumo Hospital (RSCM) along with the accuracy of referral. We also aim to evaluate the types of referral, origin of referral, referring healthcare facility and quality of referring healthcare facility. Method: The design of this study was a cross sectional design which described the accuracy of obstetrics referred cases in Emergency Unit Dr. Cipto Mangunkusumo Hospital from 2013 to 2014. Result: The total referred obstetric cases in 2013 was 1,645 patients. It was consisted of 1,307 appropriate (79.5%) and 338 inappropriate (20.5%) referred cases. Primary healthcare and general hospital were the most often referring cases to RSCM during two consecutive years. The top three cases referred to RSCM in both 2013 and 2014 were preterm premature rupture of membrane (PPROM), continued by severe preeclampsia and preterm labor. Conclusion: The number of referral cases in Indonesia is considered high, particularly in RSCM as the tertiary healthcare facility. There are still a high number of inappropriate referrals originating from primary healthcare facilities, pointing to the fact that the referral system is not running according to design or plan. To improve the quality of referral system, proper monitoring and evaluation of referral should be performed by local health department. [Indones J Obstet Gynecol 2016; 4-2: 64-66] Keywords: maternal case, referral system